PENINGKATAN PENGETAHUAN REMAJA MENGENAI PEMENUHAN GIZI SEIMBANG MELALUI ISI PIRINGKU DI MAN 1 SURAKARTA - Harisma Kusumawardani; Luluk Ria Rakhma; Nadia Aqiela Laili; Aliya Maharani Putri; Dwi Anggraini; Shofi Mela Rosida; Khantsa Mastura; Rara Rahma Fadilla; Chindi Astuti Anjellia Salsabila (Jurnal Abdi Insani, 2022)
Consumption of a balanced nutritional diet in adolescents can prevent various kinds of nutritional problems. Currently, many problems related to balanced nutrition are experienced by teenagers, which if not addressed immediately will have an impact until they are adults. Lack of knowledge in adolescents about fulfilling nutritional needs according to balanced nutrition will affect attitudes and behavior in eating wrong so that adolescent health problems arise. So teenagers need to be equipped with knowledge of how to fulfill balanced nutrition so that these health problems are resolved. To increase the knowledge of teenagers so that they can change their attitude to consume a balanced diet. By providing education and awareness of the importance of paying attention to food intake according to needs through "Fill My Plate". This community service activity method is in the form of an online webinar. The stages are pretest, socialization of material related to health problems in adolescents, screening of educational videos on the contents of my plate, discussion of questions and answers and quizzes. The subjects are 11th grade students of IPA 1-3 MAN 1 Surakarta Boarding School Program. After the material was delivered by the resource persons related to anemia, obesity, malnutrition, the contents of my plate, and the 4 pillars of balanced nutrition and a discussion session, a quiz session was then held as a measure of the success of the activity. Based on the results of the quiz test, it shows that there is an increase in knowledge of how to prepare menus that are in accordance with the contents of my plate and fulfill the needs of balanced nutrition for respondents in daily life. There is a significant difference between before and after receiving the socialization of the educational materials and videos. The increase in respondent's knowledge was seen from the results of the pretest score which obtained an average value of 2.71, while the quiz results obtained an average value of 4.84. With this increase in knowledge, respondents are encouraged to apply a healthy lifestyle and balanced nutrition according to the contents of my plate in their daily lives.